Comparison between Conventional Radiography and High Resolution Computed Tomography in Interstitial Disease of Lungs - P. Madhu; D. Santhosh (Asian Journal of Medical Radiological Research, 2020)
Background : Interstitial lung diseases are a diverse group of over 200 disease entities in which the primary site of injury is the lung interstitium. These diseases vary widely in their etiology, clinicoradiologic presentation, histopathological features and clinical course. HRCT has its limitations in the detection of interstitial lung diseases, its sensitivity is not 100% and the limitations of sensitivity are not well established. This study attempted to compare between conventional radiography and HRCT in the diagnosis of interstitial lung diseases. Subjects and Methods: All the patients were subjected to both conventional radiography and HRCT examinations and the images were viewed and analyzed. The two modalities were compared with regards to their ability to detect findings like nodular opacities, reticular opacities, septal thickening, honeycombing, lymphadenopathy etc. Results: The study has gender distribution of 60% males and 40% females. The main result of the study was that higher number of samples with findings were detected by HRCT than conventional radiography. In the detection of nodular opacity and septal thickening, the p value was less than 0.05 meaning the difference was statistically significant. Of the 30 patients, 2 had normal chest radiograms while HRCT was able to detect reticular opacities in these patients. The most common abnormality seen in both chest radiograms and HRCT was reticular opacities. The distinction between air space nodules and interstitial nodules was also much better appreciated on HRCT than on conventional radiography. In the detection of honeycombing, HRCT was much more specific being able to detect it in cases when the chest radiogram showed only reticular opacities. Even in the detection of other findings like air trapping and lymphadenopathy, HRCT scored over conventional radiography. Conclusion: HRCT therefore seems to be the investigation of choice in evaluating patients of interstitial lung disease.